항공 및 관광서비스 전공 여대생의 공감능력, 문화적 역량에 관한 연구 - 주경숙(Kyung-Sook Joo) (한국콘텐츠학회 논문지, 16(10), 2016)
This study is intended to check the empathy and cultural competence of female college students majoring in aviation and tourism service. The number of study subjects was 274. And the descriptive statistics, t-test, ANOVA, Scheffe test, and pearson correlation coefficient of data was analyzed through SPSS 20.0. According to the results of study, an average mark of empathy was $3.72{±}0.35$, and an average mark of cultural competence was $3.48{±}0.47$. When the level of difference in empathy and cultural competence was examined according to the general characteristics, the level of empathy showed a significant difference in the purpose of visiting foreign countries and foreign language skills. And the level of cultural competence showed a significant difference in religion, foreign language skills, foreign friend, experience in international exchange, experience in cultural education abroad, a method of cultural education abroad, and a necessity for cultural education abroad. With regard to correlation, there was a positive correlation between empathy and cultural competence(r=.425, p<.001). And in case of sub-attribute, it was shown that the cognitive factor and emotional factor of empathy has a positive correlation with cultural competence. It was verified that an education plan making it possible to improve cultural competence is required by checking a mutual relationship between empathy and cultural competence through these study results. 본 연구는 항공 및 관광서비스를 전공하는 여대생의 공감능력 및 문화적 역량을 확인하기 위한 것이다. 연구대상자는 274명이며, 자료는 SPSS 20.0을 통해 기술통계, t-test, ANOVA, Scheffe test, pearson correlation coefficient를 분석하였다. 연구결과는 공감능력의 평균평점 $3.72{±}0.35$, 문화적 역량의 평균평점 $3.48{±}0.47$이었다. 일반적 특성에 따른 공감능력 및 문화적 역량의 차이정도를 살펴보면, 공감능력 정도는 해외 방문목적, 외국어 실력에서 유의한 차이를 나타냈으며, 문화적 역량 정도는 종교, 외국어 실력, 외국인 친구, 외국인 교류경험, 해외 문화 교육경험, 해외문화 교육방법, 해외문화 교육필요성에서 유의한 차이를 나타냈다. 상관관계는 공감능력과 문화적 역량(r=.425, p<.001)이 순 상관관계가 있었으며, 하위속성의 경우 공감능력의 인지적 요소, 정서적 요소는 문화적 역량과 순 상관관계가 있는 것으로 나타났다. 이러한 연구결과를 통해 공감능력과 문화적 역량 간의 상호관련성을 확인함으로써 문화적 역량을 증진할 수 있는 교육 방안이 요구됨을 확인하였다.